Developing a conceptual framework of household energy consumption – energy efficiency in Selangor - Maisarah, Ahmad Sofi; Salina, Daud; Sabihah, Hitam; Wan Fadzilah, Wan Yusoff; Wan Noordiana, Wan Hanafi; Maryam Jamilah, Asha’ari; Mariam, Abdul Majid (Universiti Tenaga Nasional, 2024)
Energy consumption behaviour pertains to habitual patterns displayed by individuals, businesses, and societies in utilizing energy resources. Energy efficiency is to utilise consumption of energy in a wisely and as economically as possible. Ethical practices encompass a set of principles and behaviours that align with moral and social values, promoting fairness, integrity, and responsibility in various contexts. Adhering to ethical practices in energy efficiency not only contributes to a more sustainable and responsible energy landscape but also fosters positive relationships with stakeholders and the broader community. To enable the achievement of energy efficiency, behavioural study must be conducted on the energy efficiency at the household level since residential areas contribute the highest carbon and greenhouse gas emission. This research main objective is to determine the energy consumption behavior in aspects of attitude and energy efficiency among households. It will also investigate the relationship between both variables using Spearman Coefficient Correlation analysis; and how household ethical practices moderate its relationship using the Moderator Analysis. A set of questionnaires is use in surveying 348 households from nine districts in Selangor. This research outcomes will be beneficial for policymakers, especially in energy industry to understand how household behave to achieve efficiency energy consumption.